The comparison of interactive 3D visualization between static and animated approaches for learning binary tree topic / Mohd Zulhisam Yaakub - Yaakub, Mohd Zulhisam (2016)
Growth of three-dimensional (3D) visualization technology in computer science has led to more research into teaching and learning in instructional environments and content areas. The implementation of Computer-Assisted Instruction (CAI) in learning results in benefits as medium offers to provide specific dynamic representation. However, the research has not consistently considered instructional approaches for learning algorithm lesson, and some researches indicated that utilized methods might not be enough. The purpose of this study is to compare score performance of students enrolled in a binary tree lesson using two types o f 3D visualization approaches in CAI which are 3D static and 3D animated. An experiment was conducted to determine which of those two methods of presenting a 3D visualization would enhance student achievement and spatial abilities. The Instructional Design Model (IDM) and ADDIE model were applied to achieve the objectives of the study. In addition, usability evaluations using the CAI also investigated. The study participants were undergraduate students randomly selected from the Faculty of Computer Science and Information Technology (FCSIT), Universiti Malaysia Sarawak (UNIMAS). The assessment was divided into two groups using quasi-experimental evaluation. The control groups (Co) received CAI that provided 3D static instruction while the experimental groups (Ex) subjected via 3D animated instruction. Statistical tests used to achieve the study designs were the independent-samples t-test and pair-samples ttest. The results of the study have indicated that there was a statistically significant difference in the pre-test scores of students receiving 3D animated instruction and 3D static instruction while other results show no statistically significant difference between the post-test scores of students receiving 3D animated instruction and 3D static instruction. However, there was a statistically significant difference in students’ increment scores between students receiving 3D static instruction and student receiving 3D animated instruction. This shows that both 3D visualization methods implemented in this study can increase the student learning achievements and spatial abilities. Overall results have shown that the 3D visualization approach in CAI is effective and fulfils usability needs.